The Development of Instrument for Identifying Linguistic Intelligence of Autistic Children Aged 4-5 Years at Kindergarten of Tursina Banyuwangi In 2022/2023 Academic Year - Atmi Prawuri; Nanik Yuliati; Senny Weyara Dienda Saputri (Lafadz Jaya Publisher, 2024)
Developing linguistic intelligence in children with autism is one way to prepare children with autism so that they have a strong foundation for further development. For this reason, teachers need efforts to understand linguistic intelligence in children with autism, both through analyzing theories related to children's linguistic intelligence and identifying the linguistic intelligence of autistic children. This research aims to develop an instrument for identifying linguistic intelligence in children with autism aged 4-5 years at Tursina Kindergarten, Banyuwangi. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) approach. The analysis stage produced 6 indicators of linguistic intelligence in children with severe autism aged 4-6 years. The design stage produces an instrument design in the form of short statements and orders. The development stage developed an instrument in the form of a checklist with 5 assessment scales after going through revisions based on the results of the FGD with 3 validators. The implementation stage involves testing the instrument in class by the teacher, and the evaluation stage is carried out by asking for a qualitative assessment from the teacher. The results show that the instrument is suitable for the conditions of children with severe autism aged 4-5 years, with the note that implementation requires conducive conditions for the child. This research contributes to the development of methods for identifying linguistic intelligence in children with autism and can be a guide for teachers in supporting the development of children with autism.